Government expenditure on key sectors of the economy and stock market performance in Nigeria - Osagie Osifo; Success Osamede Abusomwan (Journal of Enterprise and Development (JED), 2023)
Purpose — This study examines the effect of Government Expenditure (GE) on key sectors of the economy and Stock Market Performance (SMP) in Nigeria.Method — Statistics Bulletin published by the Central Bank of Nigeria (CBN) was utilized as source for time series data between 1980 and 2021. SMP is proxied with MCAP and ASI while expenditure on agriculture, defense, education, and health formed components of government expenditure. The FM-OLS and ARDL methodology were adopted to determine the GE's short and long-term impact on SMP in Nigeria. ADF unit root testing, correlation analysis, Engle and Granger co-integration analysis, and preliminary descriptive statistics testing were all carried out.Result — The outcome indicates that all through the long and short term, GE on education, defense and agriculture have significant influence of SMP in the long run via MCAP channel. GE on defense and agriculture significantly affects SMP in the short run via ASI channel. Hence, this study concludes that GE components are key determinants in explaining the effect of government spending on SMP in Nigeria. The magnitude of this effect is a function of stock market proxy used.Contribution — This study provides empirical evidence on the impact of government spending on key sectors of the economy on stock market performance in Nigeria using two proxies (market capitalization and all share index) in short run and longrun.